Fabrication of ThN Using a Carbothermic Reduction to Nitridation Process. Issue 12 (12th September 2016) - Parkison, Adam J.; Parker, Stephen S.; Nelson, Andrew T.
Abstract : A carbothermic reduction to nitridation process was developed which is capable of producing high‐purity thorium mononitride (ThN) in bulk quantities. This was accomplished through study of three distinct processing routes using thermogravimetric analysis. The information gathered was then used to guide development of a draft process, which was tested within a tungsten production furnace. Scaling issues were identified and corrected following the draft process. Finally, a partitioned process was developed in response to the draft process which separates the reduction from the nitridation and carbon cleanup steps. This partitioned process was demonstrated to be capable of producing phase‐pure ThN, with oxygen and carbon impurities of 990 ± 130 wppm and 240 ± 30 wppm, respectively.